Candidatus Liberibacter asiaticus encodes a functional BolA transcriptional regulator related to motility, biofilm development, and stress response - Zhan, Xuanlin; Huang, Guoyi; Su, Jun; Zhang, Jingtian; Huang, Qiting; Deng, Xiaoling; Xu, Meirong (Frontiers in Microbiology, 2026)
“Candidatus Liberibacter asiaticus” (CLas) is an uncultivable α-proteobacterium causing the most destructive and currently incurable citrus disease, Huanglongbing (HLB). The transcription factors (TFs) of CLas are involved in various biological processes. However, the functions of most TFs remain unverified. BolA is reported to be an important transcriptional regulator related to bacterial growth and virulence. Here, the role of BolA in CLas was investigated using gene deletion and complementation assays in the heterologous host Sinorhizobium meliloti (Sme). The results showed that BolACLas and BolASme are similar in sequence and transcriptional regulation. BolA positively regulates biofilm formation—evidenced by the significant downregulation of a key gene (cyaA) in the mutant (ΔBolASme), without affecting bacterial growth. The upregulation of 16 differentially expressed genes (DEGs) related to flagellar assembly indicated that BolA negatively regulates CLas motility. BolA deletion also led to the downregulation of ABC transporters (15 DEGs) and lipid metabolism genes (13 DEGs), correlating with reduced stress tolerance. Furthermore, BolACLas is involved in modulating heme metabolism, as well as protein export, folding, sorting, and degradation. Finally, in vivo screening identified two compounds as BolA inhibitors, which significantly reduced CLas titer in infected periwinkle leaves. Taken together, this study constitutes a relevant step toward the understanding of CLas virulence by demonstrating that BolA is a key TF involved in biofilm formation, stress response, motility, and bacterial physiology, thereby presenting a potential target for disease control.